2008
DOI: 10.1118/1.2968102
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculations of correction factors for plane‐parallel ionization chambers in clinical electron dosimetry

Abstract: Recent standard dosimetry protocols recommend that plane-parallel ionization chambers be used in the measurements of depth-dose distributions or the calibration of low-energy electron beams with beam quality R50 <4 g/cm2. In electron dosimetry protocols with the plane-parallel chambers, the wall correction factor, Pwall, in water is assumed to be unity and the replacement correction factor, Prepl, is taken to be unity for well-guarded plane-parallel chambers, at all measurement depths. This study calculated Pw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…At larger depths, due to the blurring of the spectral electron fluence, also the total fluence is strongly changing even with small chamber shifts. Therefore, neglecting the nonwater equivalence of the entrance window, wall perturbation corrections of 10% and more at the half value depth may result for low electron energies, as also reported for example by Buckley and Rogers, 14 Araki,11 or Verhaegen et al 13 Shifting the NACP-02 chamber by an amount ⌬z = −0.058 cm toward the focus, the electron fluence within the chamber and the bare cavity bears the largest resemblance independent of the depth within the water phantom and independent of the energy of the primary electrons. The resulting depth dependence of p wall is within 1% even for the lowest electron energy used in this study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…At larger depths, due to the blurring of the spectral electron fluence, also the total fluence is strongly changing even with small chamber shifts. Therefore, neglecting the nonwater equivalence of the entrance window, wall perturbation corrections of 10% and more at the half value depth may result for low electron energies, as also reported for example by Buckley and Rogers, 14 Araki,11 or Verhaegen et al 13 Shifting the NACP-02 chamber by an amount ⌬z = −0.058 cm toward the focus, the electron fluence within the chamber and the bare cavity bears the largest resemblance independent of the depth within the water phantom and independent of the energy of the primary electrons. The resulting depth dependence of p wall is within 1% even for the lowest electron energy used in this study.…”
Section: Discussionmentioning
confidence: 72%
“…The presence of an energy and depth dependence of perturbation corrections for parallel-plate chambers in clinical electron dosimetry has been shown in recent years by several authors. 13,14,11,12,22 These investigations have also demonstrated that the calculated perturbation corrections are quite sensitive to small variations in the positioning of the parallelplate chamber, especially at depths larger than the reference depth z ref .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] In this work, the EGSnrcMP code system 5 is used to calculate twodimensional ͑2D͒ dose rate distributions around the BEBIG 60 Co HDR sources in an unbounded liquid water phantom in Cartesian format. The calculated dose rate data are compared to GEANT4-based published data.…”
Section: Introductionmentioning
confidence: 99%
“…6(a) by both SCDD and Si-D. Recent papers [33][34][35][36] showed that perturbation factors in electron beams can be nonunity also for "well-guarded" plane-parallel ionization chambers and their values depend on the measurement depth. Such a dependence should be accounted for when measuring depth dose distributions.…”
Section: Iiib Depth Dose Curvesmentioning
confidence: 99%